2004
DOI: 10.1023/b:ddas.0000042262.14969.2d
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Polymorphism in the Interleukin-1 Receptor-1 Gene Is Associated with Increased Risk of Helicobacter pylori Infection but Not with Gastric Cancer

Abstract: The proinflammatory cytokine interleukin-1 has been implicated in host susceptibility to Helicobacter pylori-associated disease. Recent studies suggest that this susceptibility may be under genetic control. It remains to be determined whether the relationship between IL-1 gene polymorphism and gastrointestinal disease in patients with H. pylori infection is due to the role of IL-1 in determining susceptibility to H. pylori infection per se or to the development of distinct pathological lesions. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…estimate of HWE that differed from that presented for four studies: for IL1B-31 and IL1B-511 in Chang et al (32), for IL1B-511 in El-Omar et al (18), for IL1B-511 in Gatti et al (17), and for IL1B-511 in Hartland et al (38). We did IL1B-511 and IL1B-31 meta-analyses including and excluding studies deviating from HWE and obtained similar results.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…estimate of HWE that differed from that presented for four studies: for IL1B-31 and IL1B-511 in Chang et al (32), for IL1B-511 in El-Omar et al (18), for IL1B-511 in Gatti et al (17), and for IL1B-511 in Hartland et al (38). We did IL1B-511 and IL1B-31 meta-analyses including and excluding studies deviating from HWE and obtained similar results.…”
Section: Discussionsupporting
confidence: 64%
“…In 10 studies (5,13,25,26,30,32,35,36,38,39), the mean age of controls and cases differed (younger controls). Age and sex matching was described in nine studies and five reported matching by ethnicity (Addendum 2).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study has addressed the role of IL1R1 (also known as CD121A ) in GC and H. pylori infection. The study, conducted in a Caucasian population, showed an increased risk of H. pylori infection in those harboring the IL1R1 Hinfl A allele (OR: 2.01, P -value: 0.009) but failed to show an association with GC (76). In addition, a recent meta-analysis on the endogenous receptor antagonist IL-1RA has shown the IL1RN*22 genotype to increase the risk of gastric precancerous lesions, supporting a role for this polymorphism in the early stages of gastric carcinogenesis (OR: 2.27, 95% CI: 1.40–3.70) (77).…”
Section: Inflammation In Gastric Cancermentioning
confidence: 89%
“…There is further evidence that genetic variants in the IL-1 cluster may have an influence on susceptibility to infection in Caucasians as well. Hartland and coworkers reported a significant association of the IL-1R1 Hinfl A allele with susceptibility to infection in a large cohort from the United Kingdom [34]. Since we used blood donors as controls who carry antibodies against H. pylori in 35% [17] our results concerning susceptibility to infection have to be regarded with constraints.…”
Section: Discussionmentioning
confidence: 99%